How should we divide the pie? Equity distribution and its impact on entrepreneurial teams - Breugst, Nicola; Patzelt, Holger; Rathgeber, Philipp (Journal of Business Venturing, 2015)
Drawing on a multiple case study approach and data on eight entrepreneurial teams observed over six months this article develops a dynamic model of the consequences of equity distribution among team members. Perceived justice of equity distribution emerged as a key variable influencing entrepreneurial team interactions and important entrepreneurial outcomes. High perceived justice triggered positive team interaction spirals, whereas low perceived justice triggered negative interaction spirals. Teams exposed to external threats drifted from a positive spiral to a negative spiral despite high perceived justice. We discuss the implications of our study for research on entrepreneurial imprints, justice, and exit.